The Effect of ESG on Indices’ and Firms’ Performance. A Global and an Egyptian Context. - Abdelmalak, Demiana (AUC Knowledge Fountain, 2024)
Over the years, ESG (environmental, social, and governance) investing has been increasingly adopted by the financial markets. In this paper, we aim to study the effect of ESG on Indices’ and Firms’ performance using Morgan Stanley Capital International (MSCI) Indices as a global reference and Egypt’s indices as a national reference. We also study the effect of ESG scores on the Egyptian Firms’ performance over the past 16 years using econometrical models and Fama- French Five Factors Model. Our research shows mixed results which are aligned with the existing literature review. However, one can conclude that there is a positive significant relationship between the total ESG score and the excess return of the Egyptian stocks, using Fama-French five factors model.